Fast vergence eye movements are disrupted in Parkinson's disease: A video-oculography study - Hanuška, Jaromír; Bonnet, Cecilia; Rusz, Jan; Sieger, Tomáš; Jech, Robert; Rivaud-Péchoux, Sophie; Vidailhet, Marie; Gaymard, Bertrand; Růžička, Evžen (Parkinsonism & related disorders, 2015)
BACKGROUND: Blurred near vision is a common non-motor symptom in patients with Parkinson's disease (PD), however detailed characterization of vergence eye movements (VEM) is lacking. METHODS: Convergence and divergence were examined in 18 patients with PD and 18 control subjects using infrared video-oculography. VEM metrics analyzed included latency, velocity and accuracy, in vertical and horizontal planes. RESULTS: The latency of convergence and divergence was significantly increased in PD subjects. Additionally, divergence was slow and hypometric, while other convergence metrics were similar to controls. CONCLUSION: We provide evidence in favor of disrupted VEM in PD.
Keywords: Vergence eye movements; pohyby očí; audiovizuální záznam; Humans; Video Recording; lidé středního věku; Eye Movements; Female; Aged; dospělí; senioři; lidé; Photic Stimulation; světelná stimulace; poruchy hybnosti oka; Parkinson's disease; Adult; ženské pohlaví; Ocular Motility Disorders; Male; Middle Aged; Convergence; Divergence; mužské pohlaví; Parkinson Disease; Parkinsonova nemoc